Academic Self-Efficacy as a Mediator: Examining the Link Between Career Calling and Employability in Higher Education - Mulyana, Olievia Prabandini; Izzati, Umi Anugerah; Mulyana, Phonny Aditiawan; Nucahyanie, Yunia Dwie; Puspitadewi, Ni Wayan Sukmawati; Budiani, Meita Santi (Universitas Ahmad Dahlan, 2025)
In today's increasingly competitive job market, employability has become a vital competency for students. This study examined the relationship between career calling and student employability, with a particular focus on the mediating role of academic self-efficacy. Utilizing a quantitative correlational design, the research involved 703 student participants. Data were collected through validated Likert-type instruments measuring career calling, academic self-efficacy, and employability. Path analysis conducted using JASP software revealed significant positive associations among the three variables. Mediation analysis demonstrated that career calling had a direct effect on employability (direct effect = 0.112, p = 0.002), as well as a stronger indirect effect through academic self-efficacy (indirect effect = 0.549, p < 0.001). These findings underscore the pivotal role of academic self-efficacy as a mediator, suggesting that its influence on employability is more substantial than the direct effect of career calling alone.